Episodic eolian sand deposition in the past 4000 years in Cape Cod National Seashore, Massachusetts, USA in response to possible hurricane/storm and anthropogenic disturbances - Forman, Steven L. (Frontiers in Earth Science, 2015)
The eolian sand depositional record for a dune field within Cape Cod National Seashore, Massachusetts is posit as a sensitive indicator of environmental disturbances in the late Holocene from a combination of factors such as hurricane/storm and forest fire occurrence, and anthropogenic activity. Stratigraphic and sedimentologic observations, particularly the burial of Spodosol-like soils, and associated 14C and OSL ages that are concordant indicate at least six eolian depositional events at ca. 3750, 2500, 1800, 960, 430, and <250 years ago. The two oldest events are documented at just one locality and thus, the pervasiveness of this eolian activity is unknown. However, the four younger events are identified in three or more sites and show evidence for dune migration and sand sheet accretion. The timing of eolian deposition, particularly the initiation age, corresponds to documented periods of increased storminess/hurricane activity in the North Atlantic Ocean at ca. 2.0–1.6, and 1.0 ka and also a wetter coastal climate, which suppressed the occurrence of forest fire. Thus, local droughts are not associated with periods of dune movement in this mesic environment. Latest eolian activity on outer Cape Cod commenced in the past 300–500 years and may reflect multiple factors including broad-scale landscape disturbance with European colonization, an increased incidence of forest fires and heightened storminess. Eolian systems of Cape Cod appear to be sensitive to landscape disturbance and prior to European settlement may reflect predominantly hurricane/storm disturbance, despite generally mesic conditions in past 4 ka.